2019
DOI: 10.1093/jn/nxz122
|View full text |Cite
|
Sign up to set email alerts
|

Relatively Low Maternal Aflatoxin Exposure Is Associated with Small-for-Gestational-Age but Not with Other Birth Outcomes in a Prospective Birth Cohort Study of Nepalese Infants

Abstract: Background Exposure to aflatoxin has garnered increased attention as a possible contributor to adverse birth outcomes. Objective The objective of this study was to investigate the relation of maternal aflatoxin exposure with adverse birth outcomes such as birth weight, birth length, anthropometric z scores, low birth weight (LBW), small-for-gestational-age (SGA), stunting, and preterm birth (PTB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Finally, there is a need for longitudinal cohort studies, complemented with total diets data to examine exposure to mycotoxins across the different stages of lactation, particularly in light of mixed evidence regarding their effects on birth outcomes including small‐for‐gestational age (SGA), infant growth faltering and stunting (Andrews‐Trevino et al, 2019; Hoffman et al, 2018; LeRoy et al, 2018; Passarelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is a need for longitudinal cohort studies, complemented with total diets data to examine exposure to mycotoxins across the different stages of lactation, particularly in light of mixed evidence regarding their effects on birth outcomes including small‐for‐gestational age (SGA), infant growth faltering and stunting (Andrews‐Trevino et al, 2019; Hoffman et al, 2018; LeRoy et al, 2018; Passarelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In low-and middle-income countries (LMICs), the framing of food security and nutrition problems increasingly encompasses not only undernutrition, but also diet quality (1) and overweight and obesity, with their attendant chronic diseases (2,3) . Concern for the safety of the food supply, including microbiological and mycotoxin contamination (4,5) and potentially risky additives (6) , are emerging concerns of food policy in LMICs. Detailed information on individual food consumption, collected in a survey that is appropriately representative of the relevant population, is critical for making informed policies and developing effective programmatic responses to assure nutritional health (7,8) ; lack of individual level dietary data is a barrier to developing effective solutions (9) .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found the mutagenic effect of in utero AF exposure in 14-day-old C57BL/6 mouse embryos was 20-fold greater than in parallel-dosed adult mice [27]. While there are relatively few human studies examining the relationship between AF exposure and foetal outcomes, a limited number of studies have demonstrated an association between maternal exposure and lower infant birthweight, small for gestational age [28][29][30][31][32] and subsequent stunted growth [33].…”
Section: Introductionmentioning
confidence: 99%